Translation Between Mathematical Representation: How Students Unpack Source Representation? - Dwi Rahmawati (IAIN Ambon, 2019)
Abstrak Penelitian ini bertujuan untuk memeriksa aktrivitas mahasiswa pada tahap unpack the source ketika melakukan translasi representasi verbal ke grafik. Penelitian ini merupakan penelitian deskriptif kualitatif. Subjek penelitian ini adalah 20 mahasiswa pendidikan matematika. Data dikumpulkan melalui tes disertai think aloud. Hasil penelitian menunjukkan bahwa aktivitas mahasiswa dalam membongkar sumber (unpack the source) adalah membaca masalah dengan teliti, menggambar skema dari situasi verbal, mengidentifikasi hal yang diketahui, mengidentifikasi hal yang ditanyakan, meninterpretasi informasi dan mengidentifikasi informasi baru. Abstract This study aimed to examine the activity of students in unpacking the source during the translation process of verbal to the graph representations. This research was a qualitative descriptive study. Subject of this study are twenty students of mathematics education program. The data were collected through the think-aloud test. The results showed that the activities of students in unpacking the source are reading the questions carefully, drawing the scheme of the verbal situation, identifying the things that are known, identifying the things that are asked, interpreting information and identifying new information. Schemes facilitate students in unpacking the source. The results of this research can be used as consideration to minimize the difficulties of students in unpacking the source when performing translation of verbal to the graph representation. This research is also limited to the representation translation from verbal to graph representation, has not examined the other representation such as verbal to symbolic or otherwise. So, those problem can be examined in the next research.